The impact of unilateral climate policy with endogenous plant location and market size asymmetry - Francesca Sanna-Randaccio; Roberta Sestini (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper analyses the impact of unilateral climate policy on firms' international location strategies in emission-intensive sectors, when countries differ in terms of market size. The cases of partial and total relocation via foreign direct investment are separately considered. A simple international duopoly model highlights the differences between short-term and long-term effects. In the short-term no change in location is a likely outcome in very capital-intensive sectors, and when there is a strategy shift this takes the form of partial instead of total relocation. In the long-run total relocation becomes a feasible outcome. However we found that, when tighter mitigation measures are introduced by the larger country and unit transport cost is high, with a pronounced market asymmetry the probability of firms not relocating abroad is high even in the long-term. The welfare implications of unilateral environmental measures are assessed considering global industrial pollution and accounting for shifts in location strategy.
Keywords: F12; F23; Q58; 330; Foreign Direct Investment; Carbon Leakage; Climate Policy; Relocation; Transport Costs; Welfare